Plasma Extracellular Vesicles-Derived miR-99a-5p: A Potential Biomarker to Predict Early Head and Neck Squamous Cell Carcinoma - Qiang Huang; Qiang Huang; Yu-Jie Shen; Yu-Jie Shen; Chi-Yao Hsueh; Chi-Yao Hsueh; Yi-Fan Zhang; Yi-Fan Zhang; Xiao-Hui Yuan; Xiao-Hui Yuan; Yu-Juan Zhou; Yu-Juan Zhou; et al. (Frontiers Media S.A., 2022)
Purpose: This study aimed to investigate the applicability of plasma extracellular vesicles (EVs) miR-99a-5p as a potential head and neck squamous cell carcinoma (HNSCC) diagnostic biomarker.Methods: The miRNA expression of HNSCC tissue and plasma EVs were profiled by small RNA sequencing. qRT-PCR was performed to detect miR-99a-5p expression in HNSCC (n = 93) and benign disease (n = 39) plasma EVs and formalin-fixed and paraffin-embedded (FFPE) tissue (n = 110). We constructed receiver-operating characteristic curves to investigate the diagnostic efficiency of plasma EVs miR-99a-5p.Results: Tumor tissue exhibited lower miR-99a-5p than para-tumor tissue. Patients with high miR-99a-5p expression exhibited significantly more p16 positive status. In contrast, HNSCC plasma EVs harbored more miR-99a-5p than the benign disease group. Plasma EVs miR-99a-5p distinguished HNSCC with area under the curve (AUC) of 0.7494 (95% CI: 0.6692-0.8296; p < 0.0001), with 61.54% sensitivity and 75.27% specificity, respectively. Furthermore, plasma EVs miR-99a-5p also distinguished early HNSCC with AUC of 0.7394 (95% CI: 0.6284-0.8504; p = 0.0002), with 79.07% sensitivity and 61.54% specificity, respectively.Conclusion: Plasma EVs miR-99a-5p is a potential biomarker for predicting early HNSCC.